MERDEKA CURRICULUM: APPROACH, RESULTS, CHALLENGES AND STUDENT RESPONSES TO ASSESSMENT AT TARUNA BUMI KHATULISTIWA HIGH SCHOOL KUBU RAYA - Thomy Sastra Atmaja (Jurnal Scientia, 2023)
This research was conducted to determine the assessment approach strategy, results, challenges and student responses in carrying out independent curriculum assessments at Taruna Bumi Khatulistiwa High School, Kubu Raya. Independent curriculum modifications require adaptation from teachers and students. Challenges and difficulties are things that cannot be avoided, especially since the independent curriculum is a new curriculum implemented in every educational unit. However, Taruna Bumi High School has implemented an independent curriculum for the past 3 years. This research was also conducted to find out the strategies, results and challenges faced by teachers and students. This research uses descriptive qualitative methods. Data collection uses observation, interview and documentation techniques. Data analysis according to Milles and Huberman. The implementation of the research focuses on the formulation of the problem that has been previously determined. The results of this research include that the independent curriculum has more student activities to produce products or works through co-curricular activities. Teachers assess students' ability to complete these assignments and projects, and provide feedback that supports their development. Taruna Bumi Khatulistiwa High School teachers ask students to create portfolios that reflect their abilities and achievements in their chosen subjects. This portfolio may contain writing samples, presentations, artwork, or reflective notes. Through portfolios, teachers can see student development over time and evaluate their progress in achieving learning goals. This form of assessment results involves observation, work products, and self-assessment. The results of the assessment provide freedom to determine the results of the assessment itself. The selection of the form of assessment results must consider the learning objectives, assessment criteria, and students' needs in developing their understanding and skills. that student responses may vary and some students may require adjustments or additional support in facing this more holistic and creative assessment.